Clutter Loss Modelling for Low Elevation Link Scenarios - Pavel Valtr; Jan Zeleny; Pavel Pechac; Martin Grabner (International Journal of Antennas and Propagation)
An analysis of the accuracy of several deterministic and semideterministic propagation models related to calculating clutter loss for low elevation links is presented. Predictions are compared with measurements carried out at 2 GHz over three locations. By comparing prediction and measurement techniques, improved predictive capabilities of deterministic models are demonstrated and quantified in cases where a description of the propagation environment exists and an air-to-ground scenario is considered.